Nutritional status and intake in patients with non-cystic fibrosis bronchiectasis (NCFB) - a cross sectional study. Issue 9 (September 2021) - King, Linsey; White, Helen; Clifton, Ian; Spoletini, Giulia; Ispoglou, Theocharis; Peckham, Daniel G.
Summary: Background & aims: Bronchiectasis is a heterogeneous, chronic respiratory condition, in which the role of nutrition remains unclear and nutritional guidance is lacking. Few studies have explored the role of nutrition in disease management, and little is known about nutritional requirements during periods of stability or metabolic stress. The aim of this study was to characterise nutritional status and intakes in a cohort of patients and identify potential associations with body composition and functional capacity. Methods: A prospective observational cohort study was undertaken in an adult population (>17 years). Bronchiectasis was confirmed by high-resolution computerised tomography (HRCT). Anthropometric (weight, height, Body Mass Index (BMI), triceps skinfold thickness (TSF), mid upper-arm circumference (MUAC) and mid arm muscle circumference (MAMC)] lung function and nutritional intakes were measured. Results were analysed as a whole and by disease aetiology [primary ciliary dyskinesia (PCD), Idiopathic cause (IC), bronchiectasis in association with asthma and other] and associations tested. Results: In total, 128 participants (65.5% female) completed the study. Median handgrip strength (HGS) in the total sample was only 66.5% (IQR 60.5–89.8) of reference population norms and was low for those with PCD [58.0% (IQR 43.5–70.0))]. Univariate regression indicated that BMI was a statistically significant predictor of lung function in the whole population with HGS and weight identified as statistically significant predictors of lung function in PCD. The total population and each sub-group failed to meet estimated average requirements for energy but exceeded the Reference nutrient intake (RNI) for protein. Vitamin D was consistently <35% of the RNI. Conclusion: BMI lay within normal to overweight ranges within the whole population and sub-groups, but masked important functional, body composition and nutritional deficits. This was particularly so within a younger sub-group with PCD, who had impaired muscle function, when compared to other causal and associative diseases.